Analisis Persepsi Siswa Terhadap Implementasi Kurikulum Merdeka Dalam Pembelajaran Matematika - Zulfin Nissa Fathiaz Zahra; Wiwin Astuti (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
The impact of learning with an independent curriculum can make students more interested in learning because there are new things such as often being in groups and students are more active, but there are problems in the learning process. Where the independent curriculum itself is a curriculum that places more emphasis on the character and competence of students. So student perceptions here are very important because the aim is to determine their perceptions regarding the implementation of the independent curriculum in mathematics learning regarding positive and negative impacts on students. This research uses a qualitative descriptive method. The results of the research show that the independent curriculum has a positive impact on students, but apart from that, several things mean that the implementation of the independent curriculum has not run optimally.